1990
DOI: 10.1002/hep.1840120312
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of extracellular matrix proteins in rat liver during development

Abstract: The expression and localization of extracellular matrix proteins in rat liver was investigated as a function of liver development. Levels of extracellular matrix proteins were measured by dot-blot or immunoblot protocols using monospecific antibodies prepared against collagen types I, III and IV; laminin; fibronectin; and fibronectin receptor. Proline and hydroxyproline levels from extracted liver collagen were quantitated by Pico Tag analysis. It was observed that the content of type IV collagen and fibronect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…3 The cellular sources of individual ECM proteins in liver have been reported to be derived from hepatocytes, lipocytes and sinusoidal cells. 4 As is well known, the liver is particularly affected by alcohol toxicity; important changes may occur in liver histology and its ECM with alcohol treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The cellular sources of individual ECM proteins in liver have been reported to be derived from hepatocytes, lipocytes and sinusoidal cells. 4 As is well known, the liver is particularly affected by alcohol toxicity; important changes may occur in liver histology and its ECM with alcohol treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5 Type IV collagen, found in hepatic sinusoids, promotes hepatocyte proliferation, 6 but it inhibits the further proliferation of the liver cells in the postnatal period. 4 TN and type IV collagen have an important role in liver development and growth, and tissue damage. Therefore, these ECM components were selected for study.…”
Section: Introductionmentioning
confidence: 99%
“…During liver development, collagen IV and laminin were present in the hepatic PSP in the form of discontinuous deposits. The proportion of collagen IV increases with gestational age and equals that of laminin during the early postnatal period [Reif et al, 1990;Elkasaby et al, 1991;Baloch et al, 1992;Amenta and Harrison, 1993;Ober and Lemaigre, 2018]. Studies of rat fetal livers showed that in early stages of hepatogenesis and in the postnatal regenerating liver, the sinusoids were covered with a continuous endothelium but without morphologically recognizable BM, despite the presence of collagen IV and laminin in the PSP [Amenta and Harrison, 1997;Shiojiri and Sugiyama, 2004;Zeisberg et al, 2006;Kuo et al, 2012;Mak et al, 2013;Zhou et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The main ECM components are collagens I, III, and IV. In addition, matrix glycoproteins, fibronectin, laminin, and heparan sulfate proteoglycan are present in considerable amounts [Hirata et al, 1983;Reif et al, 1990;Elkasaby et al, 1991;Martinez-Hernandez and Amenta, 1993a;Gersdorff et al, 2005;Shoulders and Raines, 2009;Mao et al, 2015]. Collagens I, III, and IV and laminin provides an environment that favors the extension of nerves and blood and lymph vessels within the organ [Amenta and Harrison, 1997;Kim et al, 1997;Tiniakos et al, 2008;Mak et al, 2012].…”
Section: Distribution Of Collagen I Iii and Iv And Laminin In The Hmentioning
confidence: 99%
“…Of special concern in the context of this epidemic is the escalating trend in the prevalence of childhood overweight and obesity on a global scale. There are several reports on the increasing prevalence of childhood obesity in industrialized countries [9][10][11][12][13][14]; however, this is an emerging health problem in low- and middle-income countries as well [15][16][17][18]. An analysis of 450 nationally representative crosssectional surveys of preschool-aged children from 144 countries indicated that in 2010, 43 million children, 35 million of them in developing countries, were estimated to be overweight and obese, and 92 million were at risk of becoming overweight.…”
Section: Global Trends In Childhood Obesitymentioning
confidence: 99%